A comparative study of MMP‐1, MMP‐2, and TNF‐α expression in different acne vulgaris lesions. (15th July 2016) - Ozkanli, Seyma; Karadag, Ayse Serap; Ozlu, Emin; Uzuncakmak, Tugba Kevser; Takci, Zennure; Zemheri, Ebru; Zindancı, Ilkin; Akdeniz, Necmettin
Abstract: Many inflammatory mediators and cytokines play important roles in the pathogenesis of acne vulgaris (AV). Information about the roles of these factors in the pathogenesis of the disease is limited. The purpose of this study was to evaluate levels of matrix metalloproteinase‐1 (MMP‐1), MMP‐2, and tumor necrosis factor‐ α (TNF‐ α ) in AV lesions. We selected 80 patients who presented at our dermatology department with AV. Their lesions included papules, pustules, nodules, and comedones. Each specimen was evaluated by histopathology with hematoxylin and eosin staining, and subsequently by immunohistochemical analysis for MMP‐1, MMP‐2, and TNF‐ α antibodies. A statistically significant difference between lesion groups emerged for MMP‐1 ( P = 0.012) and TNF‐ α ( P = 0.029) scores. The MMP‐1 score was highest in nodules and lowest in comedones. The TNF‐ α score was also highest in nodules but lowest in papules. We conclude that different levels of MMP expression can contribute to the development of different types of acne lesion and that the amount of TNF‐ α released may contribute to lesion development. Further studies of novel treatment modalities might evaluate the different clinical types of AV.